A dandelion wish - Thorpe, Kiki (Thorpe, Kiki. Never girls, 2013)
"Mia and her friends have discovered a magical passageway to Never Land! But when her little sister Gabby goes to Never Land alone, the passageway closes up, with a fairy stuck on the Main Land side, too"--